Political Competitiveness and Fiscal Structure: A Time Series Analysis. Canada, 1870 - 2015 - J Stephen Ferris; Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate the extent to which the intensity of political competition moderates the governance issues that arise in relation to Canada's fiscal structure. By fiscal structure we mean three distinct but interrelated fiscal dimensions of the state: financial stability, long run size and short run interventions into the private economy with respect to the business cycle. The paper is distinctive in focusing on four measures of political competitiveness that reflect the degree of competition in and between national parliamentary elections: the size of the majority of the governing party in the House; the distribution of the volatility adjusted winning margins of the governing party; the proportion of electorally marginal constituencies adjusted for asymmetry between parties; and a multiparty measure of the competitiveness of elections at the constituency level. The analysis accounts for the differing time series properties of the political and economic variables and the comingling of long and short term fiscal policies in the time series data. Estimation using a sequence of ARDL models indicates that greater political competition enhances fiscal stability, speeds up convergence of government size from above on fundamentals, and helps to align fiscal deficits better with the business cycle. The potential quantitative impact of more intense electoral competition is analyzed by applying the deficit model to the period of fiscal instability that arose in the 1980's and early 1990's.
Keywords: D72; D78; H30; H50; 330; political competition; electoral competition; fiscal stability; budget composition; expenditure and tax size; debt and deficits; countercyclical policy; ARDL modeling